Inversão 2D do método eletromagnético a multifrequência com a matriz jacobiana calculada com o método auto-adjunto - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2025)
This work presents the inversion of Multi-Frequency Electromagnetic (EMMF) method data, comparing two techniques for calculating the sensitivity matrix, which is crucial for the inverse problem and is responsible for a higher computational cost. For this purpose, two-dimensional synthetic models were created to generate the data to be inverted, and in the inverse problem, interpretive model meshes with different discretizations were generated. In this study, an alternative mathematical approach was sought in the literature to optimize the calculation of the sensitivity matrix, or Jacobian, due to the high computational cost generated when using the perturbative method. The chosen method was the self-adjoint method, due to numerical characteristics of the finite element solution of the direct problem, which uses direct methods to solve the associated linear system. This technique proved to be significantly superior to the perturbative method. In simple models, the reduction in processing time was at least twofold, while in more complex models, this reduction was even greater. In addition, two other models were created to study the inversion of EMMF data: the first with two conductive bodies and the other with one resistive and one conductive body. The results obtained in the model with conductive bodies were quite satisfactory, clearly identifying the region of presence of both. In the model with one resistive and one conductive body, the result did not clearly identify the resistive body; this limitation stems from the very nature of the EMMF method, which is inductive.
Keywords: Inversão; Custo Computacional; Matriz de Sensibilidade; Método Auto- Adjunto; CNPQ:: CIÊNCIAS EXATAS